Pola Asuh Orang Tua terhadap Pembentukan Karakter dan Prestasi Belajar Siswa Kelas IV SD - Susilo, Dhini Fitrah Salsabila; Wijayanti, Murwani Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Education is an important character foundation in the development of students, especially at the Elementary School level, because it forms personality and moral values from an early age. This study aims to explore the relationship between parenting patterns and character formation and learning achievement of fourth grade Elementary School students. Using a literature study approach, data were collected and explained from various scientific journals, books, and relevant articles that discuss the influence of parenting patterns on character development and children's academic achievement. The analysis was carried out by reviewing the results of previous studies to identify general patterns and differences in the influence of each type of parenting pattern. The results showed that students who were raised with a democratic parenting pattern tended to have responsible, disciplined, and empathetic characters, which had a positive impact on academic achievement. In contrast, authoritarian and permissive parenting patterns showed obstacles in the formation of strong character and optimal academic achievement. This finding is the importance of the role of parents in supporting the development of children's character and academics through appropriate parenting patterns. Pendidikan karakter menjadi fondasi penting dalam pengembangan peserta didik, khususnya pada jenjang Sekolah Dasar, karena membentuk kepribadian dan nilai moral sejak dini. Penelitian ini bertujuan untuk menggali hubungan antara pola asuh orang tua dengan pembentukan karakter dan prestasi belajar siswa kelas IV Sekolah Dasar. Dengan menggunakan pendekatan studi literatur, data dikumpulkan dan dianalisis dari berbagai jurnal ilmiah, buku, serta artikel relevan yang membahas pengaruh pola asuh terhadap perkembangan karakter dan capaian akademik anak. Analisis dilakukan dengan mengkaji hasil-hasil penelitian sebelumnya untuk mengidentifikasi pola umum serta perbedaan pengaruh dari masing-masing tipe pola asuh orang tua. Hasil studi menunjukkan bahwa siswa yang dibesarkan dengan pola asuh demokratis cenderung memiliki karakter bertanggung jawab, disiplin, dan empatik, yang berdampak positif terhadap prestasi akademik. Sebaliknya, pola asuh otoriter dan permisif menunjukkan hambatan dalam pembentukan karakter yang kuat dan capaian akademik optimal. Temuan ini menekankan pentingnya peran orang tua dalam mendukung pengembangan karakter dan akademik anak melalui pola asuh yang tepat.